Kajian Inovatif BIPA Melalui Webinar HISKI Pusat 27 Desember 2023 - Misnawati Misnawati (FKIP Universitas Palangka Raya, 2024)
Learning Indonesian for Foreign Speakers (BIPA) is an important aspect in supporting the spread and understanding of Indonesian culture internationally. In the context of BIPA learning innovation, Prof. Uli Kozok from the University of Hawai'i at Manoa has implemented two forms of learning that emphasize two main approaches. According to Prof. Uli Kozok has two forms of BIPA learning, namely: (1) Synchronous, carried out using direct communication technology such as TV, Zoom and Skype. (2) Asynchronous, learning can be done with flexibility via the internet, such as via the world wide web (WWW). Keywords: BIPA, synchronous, and asynchronous